Evolution of drug regulations and regulatory innovation for anticancer drugs in China - Yang Liu; Ning Zhang; Cuicui Xie; Yale Jiang; Yunhe Qin; Liyun Zhou; Yi Fan; Lianjie Ren; Chen Yin; Huan Yang; Wei Xie; Qing Zhai; et al. (Elsevier, 2022)
Over the past two decades, China has introduced significant changes to drug regulations through regulatory innovations to accelerate drug review and approvals, keeping in line with the rapidly growing scientific innovation in drug research and development (R&D). In this study, we outlined the revolution of drug regulation in China since the establishment of the State Drug Administration in 1998. More particularly, we performed a comprehensive analysis of newly approved anticancer drugs in China from the year 2005 to May 2021, as a powerful illustration of how the revolution has changed the drug R&D landscape. Innovative drug development in China has boomed, benefiting in particular from pro-innovation policies as well as expedited program designations by the authority. We found a significant increase in the number of both imported and domestic new anticancer drugs from 2005 to 2021, with the emergence of drugs with novel mechanisms of action, including immune checkpoint inhibitors and cell therapy products. Drug lag has also been dramatically shortened by more than 70% for imported drugs in years 2016-2020 compared to years 2006-2010. Furthermore, we provide an insight into the potential approaches to further optimize the science-based and clinical value-based regulatory and R&D drug ecosystem in China. This review provides evidence of significant impacts of regulations and policies on drug R&D and suggests that the constantly adapting regulatory ecosystem will speed up drug development in China and worldwide.